Serum and Urinary Uromodulin in Dogs with Early Chronic Kidney Disease vs. Healthy Canine Population - Nikola Marečáková; Jana Kačírová; Csilla Tóthová; Aladár Maďari; Marián Maďar; Mária Kuricová; Slavomír Horňák (Animals, 2024)
Serum and urinary uromodulin are evaluated as potential biomarkers of kidney disease. The aim of our research was to select a more appropriate form of uromodulin for the diagnosis of early stages of chronic kidney disease (CKD). We also focused on the influence of age and gender in one breed on uromodulin and on the possible interbreed differences. Serum uromodulin had the lowest values in dogs younger than 2 years but no effect of gender, breed, or CKD was observed. Urinary uromodulin indexed to urinary creatinine was significantly reduced in dogs in stage 2 of CKD (p = 0.003) in contrast to uromodulin converted to urine specific gravity. Urinary uromodulin with both corrections was significantly lower in Belgian shepherds compared to German shepherds (p < 0.0001, p = 0.0054) but was not influenced by gender or age. In stage 1 of CKD, urinary uromodulin correlated with kidney disease markers SDMA (p = 0.0424, p = 0.0214) and UPC (p = 0.0050, p = 0.0024). Urinary uromodulin appears to be more associated with CKD than serum uromodulin. Further studies with a larger number of patients are needed for the suitability of urinary uromodulin as a marker of early-stage disease.